Bacterial wilt resistance gene Slmlo1/6 mutants in tomato created by CRISPR/Cas9 technology - SHI Jianlei1, 2, XIONG Zili1, SU Shiwen1, FU Cunnian1, ZAI Wenshan1* (Guangxi Zhiwu)
Bacterial wilt is a devastating soil-borne disease in tomato(Solanum lycopersicum)production. The pathogenic species are complex and tend to have a variation, while mlo caused by the recessive mutation of MLO genes has a broad-spectrum resistance. The previous study suggested that Slmlo1/6 may be involved in the resistance response to bacterial wilt in tomato. In order to further study the gene function of Slmlo1/6 in tomato bacterial wilt resistance, the genetic mutant plants were created by CRISPR/Cas9 technology and their phenotypes were identified followed. The results were as follows:(1)gRNA sequences of SlMLO1/6 were designed and assembled with the U6 promoters, then U6-gRNA1/6 fragments containing highly effective targets were ligated to CRISPR vector of pBGK via restriction enzyme Bsa I digestion, to construct the two-gene fusion knockout vector of pBGK-SlMLO1/6. The recombinant plasmid of pBGK-SlMLO1/6 was transformed into Escherichia coli DH5α competent cells and positive monoclonal clones were selected via plate cultivation. Using Agrobacterium tumefaciens GV3101 strains-mediated genetic transformation and resistance screening to hygromycin, a total of nine edited tomato plants were obtained with sequencing validation.(2)Target region sequencing showed that M2 and M8 plants had the 177 bp and 7 bp deletion of SlMLO1, respectively, M7 had the 12 bp deletion of SlMLO6, and M9 had a single base T insertion of SlMLO6. Except for four single gene homozygous mutants above, the other mutations were heterozygous.(3)RT-qPCR showed that compared with the wild type plant, SlMLO1/6 gene expression of the mutants was significantly decreased, especially M2, M7, and M8 plants.(4)Phenotypic identification indicated that SlMLO1/6 might be tomato bacterial wilt susceptibility genes. In conclusion, the knockout vector is successfully constructed for resistance MLO genes and tomato transformation is also achieved, homozygous mutants acquire resistance to bacterial wilt. Amino acid deletion and frameshift mutation may be the crucial reasons for the gene function change of Slmlo1/6 in resistance. The results provide a theoretical reference and genetic engineering materials for the gene function study in resistance to bacterial wilt and disease resistance breeding application of tomato.